Studi In Silico Interaksi Senyawa Bioaktif Curcuma xanthorrhiza Roxb. terhadap Protein mTOR sebagai Kandidat Terapi Antikanker - Felaisya Fani Fatihah; Romy Dwipa Yamesa Away; Arif Juliari Kusnanda (Departemen Kimia Universitas Andalas, 2026)
The mammalian target of rapamycin (mTOR) is a crucial regulator of cell growth and proliferation, making it a promising target for anticancer drug discovery. This study evaluated the potential of major bioactive compounds from Curcuma xanthorrhiza Roxb. as mTOR inhibitors using an in silico molecular docking approach. Drug-likeness was assessed based on Lipinski's Rule of Five, followed by molecular docking using Molecular Operating Environment (MOE) 2019 against mTOR (PDB ID: 4JT5), PP242 was employed as the native ligand for redocking validation and as the reference compound for molecular docking. The docking protocol was validated by redocking the native ligand, yielding an RMSD value of 1.2 Å, indicating a reliable docking procedure. Four compounds fulfilled Lipinski's Rule of Five, while xanthorrhizol exhibited a single violation related to its LogP value. Curcumin showed the strongest binding affinity with a docking score of −9,3485 kcal/mol, followed by demethoxycurcumin, bisdemethoxycurcumin, xanthorrhizol, and germacrone. Curcuminoids formed hydrogen bond and hydrophobic interactions with key active-site residues. The docking results indicate that curcumin demonstrated a favorable binding profile among the tested compounds, however, further experimental studies are required to confirm its biological activity.